Dating of the Dome Fuji, Antarctica deep ice core (scientific paper) - Watanabe, Okitsugu; Shoji, Hitoshi; Satow, Kazuhide; Motoyama, Hideaki; Fujii, Yoshiyuki; Narita, Hideki; Aoki, Shuji (国立極地研究所, 2003)
The Antarctic ice sheet preserves paleo-climate information in the form of physical and chemical stratigraphy. A deep ice core was continuously drilled down to a depth of 2,503 m at Dome Fuji station, East Dronning Maud Land, Antarctica, during the 1993-97 JARE inland operations. Oxygen isotope measurements were conducted on 7 to 50 cm-long ice core samples selected from the entire core depth. A time scale for the Dome Fuji core is calculated from past accumulation rates and an ice flow model. Past accumulation rates were converted from oxygen isotope values by using an empirical equation obtained in the Dome Fuji area. A steady-state flow model was preciously developed for a time scale calculation of the Summit ice core, Greenland. Using reference depth points from volcanic signals and annual layer thickness values measured on the Dome Fuji core allows for tuning of the calculated time scale. A depth-age profile was obtained for the past 320 kyr. The obtained paleo-temperature profile shows the characteristics of the past three glacial and interglacial periods. The power spectrum of δ^<18>O change over an interval of 320 kyr reveals three dominant cycles. The paleo-temperature profile coincides quite well with the Vostok ice core data in general but not in detail, suggesting that further studies are needed both for chronological investigations and a multi-factor, cross-correlation analysis between deep ice cores for climatological understanding. application/pdf journal article